Canadian Survey on the Provision of Child Care Services - Dafna Kohen; Leanne Findlay (Economic and Social Reports)
To date, there exists little national information on the provision of child care services in Canada, despite investments in the creation of a national child care program. Statistics Canada, in collaboration with ESDC developed the Canadian Survey on the Provision of Child Care Services (CSPCCS) to identify the feasibility of a survey frame to survey child care providers, and to enable the reporting of descriptive information about those providers. This article describes the CSPCCS and its objectives.